2014
DOI: 10.3109/01612840.2014.935901
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Attitudes about Psychiatric Mental Health Nursing

Abstract: The purpose of this study was to describe Masters entry nursing students' attitudes about psychiatric mental health clinical experiences; preparedness to care for persons with mental illness; students' perceived stigmas and stereotypes; and plans to choose mental health nursing as a career. A 31-item survey was administered to pre-licensure graduate nursing students who were recruited from a Masters entry nursing program from a university in a large city in the Midwestern US. Results indicated that clinical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 27 publications
2
52
0
4
Order By: Relevance
“…It is important that students understand the impact of stigma to ensure that they can provide the highest possible health care for consumers (Hunter et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is important that students understand the impact of stigma to ensure that they can provide the highest possible health care for consumers (Hunter et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…El avance en la comprensión de la percepción sobre vivir con esquizofrenia, y lo que esto conlleva, permite humanizar cada intervención por parte del profesional de enfermería (17), ya que puede sensibilizar la práctica y la gestión del cuidado, y es importante para evidenciar la forma en la que se concibe y se lleva a cabo la atención, visualizando con ello mecanismos para innovar las acciones del personal de salud en pro de la mejora de la calidad de vida de las personas diagnosticadas (18).…”
Section: Palavras-chaveunclassified
“…Mental health and psychiatric nursing education shows variations between countries. 16,25 Mental health and psychiatric nursing was first included in undergraduate education programs in Turkey in 1964. After the start of academic nursing and increases in the number of academic staff in nursing, nursing education started to include psychiatric nursing concepts and information rather than medical information.…”
Section: 24mentioning
confidence: 99%
“…15,16 Strengthening positive attitudes towards mental health in nursing education may contribute to the retention of nurses in this field. 4,8 It has been reported that exposure to theory and clinical experience in psychiatric nursing affect attitudes towards psychiatric patients positively, contribute to their career choices and increase their interest in mental health.…”
mentioning
confidence: 99%